HABITAT AND DISTRIBUTIONPharella acutidens (BIVALVE) IN MANGROVE FOREST OF SUNGAI CINGAM VILLAGE OF RUPAT SUB DISTRICT OF BENGKALIS REGENCY OF RIAU PROVINCE - Mirna Kumala Sari Dalimunthe; Syafruddin Nasution; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractPharella acutidens clam is a bivalve lives in mangrove ecosystem , which is one of protein source for Rupats’ people. This research was conducted in Maret 2018 located at the mangrove forest of Sungai Cingam Village, Rupat Sub District, Bengkalis Regency. This research was aimed to determine the habitat characteristics, density and distribution patterns of P. acutidens . It used survey method and sampling location determined by purposive sampling. Measurement of water quality was done by in situ and ex situ which consist of physics and chemical parameters. Habitat characteristicsof P. acutidens was muddy sand,  and sandy mud . Sediment organic matter was high 10,60-14.85%. The water quality parameters were still support for the life of the P. acutidens. The average density was 1,8-4.2 ind/m2. The highest density was in middle zone and the lowest in upper zoneof the Intertidal. The distribution pattern was grouping. While highest size of individual P.acutidens found 7cm.Keyword: Habitat Characteristics, Density, Distribution Patterns, P. acutidens.